Tingkat Pengetahuan Sadari Pada Remaja Putri - Putri, Salsa Alfianty Lasim (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Background: Breast cancer is a cancer that is the main cause of death in women worldwide. Of all diagnosed cancer cases, breast cancer was ranked second (1.7 million, 11.9%) after lung cancer (1.8 million, 13%). Early detection is a very important first step to find out early the presence of a tumor or lump in the breast so that it can reduce mortality from this cancer. Women who do BSE can find breast cancer at an earlier stage and are more likely to be treated early, thereby reducing the risk death from breast cancer. Research method: This type of research is a literary journal, using two databases, namely Pubmed and Google Scholar. The keywords used were (“adolescent” OR “adolescent”) AND (breast self-examination OR BREASE). After being selected 10 literatures consisted of 7 cross-sectional studies, 1 pre-post intervention study, 1 descriptive study, 1 descriptive and non-experimental study. Conclusion: From the results of the journal literature, the average young woman only knows what BSE is but only occasionally has never even done BSE.